Citra Perempuan Dalam Cerpen Air Karya Djenar Maesa Ayu dalam Perspektif Feminisme: Citra Perempuan Dalam Cerpen Air Karya Djenar Maesa Ayu dalam Perspektif Feminisme - Putri Viety, Okke Risvira (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
Abstract This paper discusses the image of women in Air Djenar Maesa Ayu's short story. This short story has a background in social life that occurs in society. This short story raises the main topic of women's struggles in living their lives after being abandoned by men. Social injustice like this creates various impacts such as subordination. This research uses descriptive analysis method. This study began with data collection using the mode of listening and reading short stories as a whole and then continued with data analysis using feminist study theory. This study shows that the short story Air by Djenar Maesa Ayu is included in liberal feminism. The results and discussion of this research are compiled based on issues related to women and the perspective of the reality of the text in short stories. The results of this short story analysis are divided into 3 concepts, namely: the image of women from the physical aspect, the image of women from the psychological aspect, the image of women from the social aspect. The story of the problems experienced in this short story is told through the character Saya. Based on the data and results of the analysis, the researcher describes the image of women in Djenar Maesa Ayu's short story Air through the social conflicts she experiences. Researchers add moral and social values ​​in this study. Researchers teach readers to respect each other as human beings through research on the short story Air by Djenar Maesa Ayu. Keywords: image of women, cultural background, liberal feminism, subordination